The principle of equality. Gender issues - Ivanega, Miriam Mabel (2020)
Progressivity in the exercise of rights by women is the very essence of human dignity. Reality shows female vulnerability and situations of inequality, violence, discrimination and harassment to which they are subjected. Therefore, it is essential that women have sufficient tools to access an effective protection of their rights. Argentine jurisprudence is marking a slow but positive path in respect for equality and non-discrimination.